Elevated serum IL-35 and increased expression of IL-35-p35 or -EBI3 in CD4(+)CD25(+) T cells in patients with active tuberculosis - Kong, Bin (Am J Transl Res, 2016)
Despite the recent appreciation of interleukin 35 (IL-35) function in inflammatory diseases, little is known for IL-35 response in patients with active tuberculosis (ATB). In the current study, we demonstrated that ATB patients exhibited increases in serum IL-35 and in mRNA expression of both subunits of IL-35 (p35 and EBI3) in white blood cells and peripheral blood mononuclear cells. Consistently, anti-TB drug treatment led to reduction in serum IL-35 level and p35 or EBI3 expression. TB infection was associated with expression of p35 or EBI3 protein in CD4(+) but not CD8(+) T cells. Most p35(+)CD4(+) T cells and EBI3(+)CD4(+) T cells expressed Treg-associated marker CD25. Our findings may be important in understanding immune pathogenesis of TB. IL-35 in the blood may potentially serve as a biomarker for immune status and prognosis in TB.